Coordination aspects in Schiff bases cocrystals. (15th November 2018) - Golbedaghi, Reza; Fausto, Rui
Graphical abstract: Available information on cocrystals containing Schiff bases coordinated to metal atoms is reviewed, with emphasis given to coordination aspects. Abstract: Cocrystals are materials that contain molecules of two or more compounds in a single crystal. They have been receiving applications in many fields, including paper, textile, chemical, photographic and electronic industries. However, their main uses are centered in the pharmaceutical industry, where they have been gaining importance in recent years. In this article, the scientific literature reporting structures and properties of cocrystals containing Schiff bases coordinated to metal atoms is reviewed, with emphasis given to the coordination aspects. Schiff bases are the nitrogen analogues of aldehydes or ketones in which the carbonyl group has been replaced by an imine group. They receive multiple uses, e.g., as pigments and dyes, intermediates in organic synthesis, catalysts and polymer stabilizers, and exhibit a broad range of biological activities. Cocrystallization of Schiff bases with other bioactive molecules, and their coordination with metal atoms (which per se may be relevant in terms of biological functions), then appears as a very promising strategy to produce materials of interest for a wide range of applications in pharmaceutical industry. The present review aims to highlight the available relevant information on this type of materials to those interested to work in this domain and stimulate further investigation in the field.